Multiple Plastids Collected by the Dinoflagellate Dinophysis mitra through Kleptoplastidy - Nishitani, Goh (American Society for Microbiology, 2012)
Kleptoplastidy is the retention of plastids obtained from ingested algal prey, which may remain temporarily functional and be used for photosynthesis by the predator. We showed that the marine dinoflagellate Dinophysis mitra has great kleptoplastid diversity. We obtained 308 plastid rbcL sequences by gene cloning from 14 D. mitra cells and 102 operational taxonomic units (OTUs). Most sequences were new in the genetic database and positioned within Haptophyceae (227 sequences [73.7%], 80 OTUs [78.4%]), particularly within the genus Chrysochromulina. Others were closely related to Prasinophyceae (16 sequences [5.2%], 5 OTUs [4.9%]), Dictyochophyceae (14 sequences [4.5%], 5 OTUs [4.9%]), Pelagophyceae (14 sequences [4.5%], 1 OTU [1.0%]), Bolidophyceae (3 sequences [1.0%], 1 OTU [1.0%]), and Bacillariophyceae (1 sequence [0.3%], 1 OTU [1.0%]); however, 33 sequences (10.8%) as 9 OTUs (8.8%) were not closely clustered with any particular group. Only six sequences were identical to those of Chrysochromulina simplex, Chrysochromulina hirta, Chrysochromulina sp. TKB8936, Micromonas pusilla NEPCC29, Micromonas pusilla CCMP491, and an unidentified diatom. Thus, we detected >100 different plastid sequences from 14 D. mitra cells, strongly suggesting kleptoplastidy and the need for mixotrophic prey such as Laboea, Tontonia, and Strombidium-like ciliates, which retain numerous symbiotic plastids from different origins, for propagation and plastid sequestration.